Peningkatan Komunikasi melalui Demonstrasi Bermain Alat Peraga dalam Pengembangan Kemampuan Berbahasa Sederhana pada Anak TK Pertiwi Kecamatan Kalikotes Kabupaten Klaten 2014/2015 - Sumiyem Sumiyem (Faculty of Teacher Training and Education, Universitas Muhammadiyah Surakarta, 2015)
This study aimed to describe the increase in communication through demonstration play props in simple language skills development in children kindergarten Pertiwi Kalikotes Klaten Regency second semester of academic year 2014/2015. Subject and source of research data as many as 21 students. Data collection method used observation, documentation, and testing. Analysis of data using critical and comparative analysis. Results of research and discussion were that the data obtained from precycle until the second cycle, obtained progress learning achievement of children in learning through demonstration using props, on precycle average of 72 and the first cycle by an average of 76.5 and the second cycle mean average of 84. It seems clear that an increase in the average value of precycle to the first cycle of 4.5 figure (6.3%), from the first cycle to the second cycle there is an increase of 7.5 numbers (9, 8%), from the second cycle precycle to an increase of 12 points (16.7%). The highest value precycle stage at 82 and 86 as well as the first cycle of the second cycle of 92. It is clear that from the stage of the first cycle precycle to an increase of 4 digits (4.9%), from the first cycle to the second cycle an increase of 6 figures (7%), and from the second cycle precycle to an increase of 10 points (12.2%). The lowest value obtained precycle stage at 66 and 70 as well as the first cycle of the second cycle of 76. It can be affirmed that the step of the first cycle precycle to an increase of 4 digits (6%), from the first cycle to the second cycle an increase of 6 figure (8.6%), and from the second cycle precycle to an increase of 10 points (15.2%). Percentage from precycle was obtained by 29% and the first cycle was obtained by 57% and the second cycle of 100%. It seems clear that the step of the first cycle precycle to an increase of 29%, from the first cycle to the second cycle there is an increase by 43%, and from the second cycle precycle to an increase of 71%. Thus, the learning achievement of children in learning through demonstration using props from the second cycle occurred precycle to a significant increase.